Introducing Windows server 2012 (Microsoft, 2015)
Windows Server 2012 is probably the most significant release of the W Server platform ever. With an innovative new user interface, powerful indows new management tools, enhanced Windows PowerShell support, and hundreds of new features in the areas of networking, storage, and virtualization, Windows Server 2012 can help IT deliver more while reducing costs. Windows Server 2012 also was designed for the cloud from the ground up and provides a foundation for building both public and private cloud solutions to enable businesses to take advantage of the many benefits of cloud computing. This book provides a technical overview of Windows Server 2012 and is intended to help IT professionals familiarize themselves with the capabilities of the new platform. This present edition also replaces the earlier preview edition, with screenshots and feature descriptions now being based on RTM instead of Beta.